Analysis of treatment outcomes in patients with antineutrophil cytoplasmic antibody-associated vasculitis on rituximab therapy - Tsvetelina Yoneva,; Yana Zdravkova,; Georgi Kotov,; Ekaterina Ivanova Todorova,; Georgi Vasilev,; Rasho Rashkov,; Ivan Sheytanov, (Archives of Rheumatology, 2023)
Objectives: This study aimed to analyze a group of patients with severe and refractory antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) managed with rituximab and to report on treatment outcomes. Patients and methods: A total of 78 patients (41 females, 37 males; mean age: 50.1±13.4 years; range, 18 to 76 years) with AAV on rituximab treatment were included in the single-center, retrospective study conducted between 2009 and 2018. The diagnosis was established based on the 1990 classification criteria of the American College of Rheumatology and the definitions of vasculitis of Chapel Hill Consensus Conference. Laboratory and immunological tests were conducted. Disease activity was determined through the Birmingham Vasculitis Activity Score. Results: Rituximab was preferred over cyclophosphamide in 37 patients and used as a second-line therapy after cyclophosphamide in 41 cases. Rituximab treatment showed favorable outcomes with regard to serum creatinine levels, proteinuria, and hematuria, as well as in cases of isolated lung involvement. Nearly half of patients with pulmonary renal syndrome also improved, with 22.2% achieving remission. ANCAs were positive in 85.9% of patients at the onset of rituximab treatment and became negative in 82% of the positive cases. Adverse events were rare and included infusion reactions (one case of reactivation of a herpes zoster infection and one case of allergic reaction). Conclusion: Rituximab is an efficient and safe therapeutic option in patients with AAV who are difficult to treat, have insufficient response, or have not tolerated other treatments.